2006
DOI: 10.1152/jn.01168.2005
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Mammalian Retinal Ganglion Cells With Multielectrode Arrays

Abstract: Existing epiretinal implants for the blind are designed to electrically stimulate large groups of surviving retinal neurons using a small number of electrodes with diameters of several hundred micrometers. To increase the spatial resolution of artificial sight, electrodes much smaller than those currently in use are desirable. In this study, we stimulated and recorded ganglion cells in isolated pieces of rat, guinea pig, and monkey retina. We used microfabricated hexagonal arrays of 61 platinum disk electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

58
359
8
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(433 citation statements)
references
References 72 publications
58
359
8
2
Order By: Relevance
“…5) that are about two orders of magnitude below the damage threshold current density (Butterwick et al 2007;Cohen et al 2011). These current thresholds are smaller than most reported values (reviewed in Sekirnjak et al 2006). We attribute the low threshold to the tight tissue-electrode contact and to monophasic pulses that efficiently polarize cell membranes (Plonsey and Barr 2007).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…5) that are about two orders of magnitude below the damage threshold current density (Butterwick et al 2007;Cohen et al 2011). These current thresholds are smaller than most reported values (reviewed in Sekirnjak et al 2006). We attribute the low threshold to the tight tissue-electrode contact and to monophasic pulses that efficiently polarize cell membranes (Plonsey and Barr 2007).…”
Section: Discussionmentioning
confidence: 69%
“…In the epiretinal configuration the stimulation electrode is close to the retinal projection neurons, the ganglion cells, whereas in the subretinal configuration the stimulation electrode is close to the outer retina. The activation of preselected retinal circuitry is currently investigated in both configurations: Examples include the selective activation of retinal ganglion cells with small electrodes (Sekirnjak et al 2006(Sekirnjak et al , 2008 and the preferential activation of bipolar cells or photoreceptors with sinusoidal stimuli with appropriate frequencies (Freeman et al 2010). Restricted stimulation geometry, however, hampers a thorough investigation of the biophysical mechanisms underlying neuronal stimulation in the retina (but see Fried et al 2009).…”
mentioning
confidence: 99%
“…Sekirnjak et al reported that reducing the electrode area can limit the range of stimulated retinal ganglion cells to a spatially confined region. (14) The localization of stimulation indicates that the excitation of the retina and the primary visual cortex are both localized. Thus, the localization of phosphenes is suggested to be achieved by optimizing the stimulation waveform.…”
Section: Discussionmentioning
confidence: 99%
“…(12) The optimum pulse duration and frequency for retinal ganglion cell activation (with respect to stimulation effectiveness) has been studied in vitro. (13)(14)(15) However, the optimal stimulation waveform shape remains unknown. Accordingly, a rectangular pulse may not be optimal as the stimulation waveform.…”
Section: Introductionmentioning
confidence: 99%
“…Görsel protez sistemleri, görsel yolda zarar görmüş bölgelerin bypass edilerek fonksiyonel olarak uygun bozulmadan kalan bölgelerdeki sinir hücrelerini o bölgeye yerleştirilen bir elektrot dizisi ile elektriksel olarak uyartarak görsel restorasyonun yeniden kazanımını sağlamayı hedefleyen sistemlerdir. Son yıllarda, elektronik, minyatürizasyon, malzeme, mikroelektronik paketleme gibi farklı alanlardaki ilerlemeler retina protezlerinin geliştirilmesini mümkün kılmıştır [5,6]. Retina protezleri elektriksel uyartımın gerçekleştirileceği mikroelektrot dizisinin implante edileceği hedef retina bölgesine bağlı olarak 3 ana kategoride sınıflandırılabilir.…”
Section: Gi̇ri̇ş (Introduction)unclassified